Glycan and glycosaminoglycans as clinical biomarkers and therapeutics. - Zhang, Lijuan (Progress in molecular biology and translational science ;, 2019)
Glycans and Glycosaminoglycans as Clinical Biomarkers and Therapeutics - Part B, Volume 163 in the Progress in Molecular Biology and Translational Science series, provides informative monographs on a variety of research topics related to Glycans and glycosaminoglycans as clinical biomarkers and therapeutics. Topics in this update include an Overview of Fugal Glycan-based Therapeutics, Heparin: An Essential Drug for Modern Medicine, Low Molecular Weight Heparins and Their Clinical Applications, The Clinical Use of Fondaparinux: A Synthetic Heparin Pentasaccharid, Heparinoids as Clinically Used Drugs, Marine Glycan-Derived Therapeutics in China, Efficacy of Heparinoid PSS in Treating Cardiovascular and other Diseases-30 Years Clinical Applications in China, and more.